Perlindungan Hukum Terhadap Notaris Dalam Melaksanakan Hak Dan Kewajiban Ingkar Notaris Pada Saat Penyidikan Kepolisian Negara Republik Indonesia - Erdi Erdi; Surya Perdana; Suprayitno Suprayitno (Universitas Muhammadiyah Sumatera Utara, 2020)
The police in terms of their duties as investigators can search for information from various sources and witness statements. Investigations can only be carried out if an event is believed to be a criminal offense and therefore, before an act of forced effort, then the data and facts are obtained carefully from the results of the investigation and thus the investigation is a follow-up to the activities of an investigation including an examination of Notary Public. The type of this research is normative legal research refers to library research or document study. Issues that will be examined in this study, namely the regulation of notarial summons by police investigators, the mechanism the use of denial rights and obligations of a notary public in terms of maintaining the confidentiality of the deed when examined, and the form of legal protection against the notary in terms of maintaining the confidentiality of the deed when carried out by police investigators. The results of the study showed that the regulation of notary summons by police investigators was regulated in Article 66 Paragraph 1 of the UUJN, the terms and procedure for notary summons are regulated in Article 26, Article 27 of Regulation Ministry of Law and Human Rights Number 7 of 2016 concerning the Notary Honorary Council. The mechanism is the notary can fulfill the summons after obtaining approval from the Notary Honorary Council. Legal protection for notaries is the existence of derivative proceedings